PENGAMBANGAN SISTEM NANOSTRUCTURED LIPID CARRIER (NLC) DAUN Chrysanthemum cinerariifolium (Trev.) Vis DENGAN VARIASI KONSENTRASI LIPID - Listiyana, Anik; Mutiah, Roihatul; Suyadinata, Arief; Salsabilla, Farida Rahma (Journal of Islamic Medicine, 2020)
Ethanol extract 96% of Chrysanthemum cinerariifolium (Trev.) Vis leaves are proven to have anticancer activity. However, these compounds have low solubility in water and fat. To improve the bioavailability of preparations, the development of drug design in the form of Nanostructured Lipid Carrier (NLC) is carried out.The aim this study was to determine the effect of differences in lipid concentration of Monostearin and Oleic Acid in the formulation of the NLC system of Chrysanthemum cinerariifolium (Trev.) Vis leaves, which produced good physicochemical characteristics including organoleptic characteristics, pH, viscosity, particle size, and drug entrapment efficiency. Making is done using the High Shear Homogenization method. Organoleptic tests showed ideal results for the Nanostructured Lipid Carrier (NLC) system, the resulting pH values in formula 1 (7.0 ± 0.12), formula 2 (6.7 ± 0.17) and formula 3 (6.8 ± 0.2)), the viscosity value of formula 1 (55.66 ± 2.84 cPs), formula 2 (28.86 ± 3.91 cPs), and formula 3 (28.57 ± 16.85 cPs). Particle size of formula 1 (5530 ± 320.47 nm), formula 2 (5337 ± 671.44 nm) and formula 3 (4676 ± 2215.75 nm)). The entrapment efficiency value of formula 1 drugs (33.55%), formula 2 (38.77%), formula 3 (83.75%). Based on the characterization result, the best formula was obtained at a lipid concentration of 10%, which was used for the formula of the NLC system of Chrysanthemum cinerariifolium (Trev.) Vis leaves for oral anticancer preparations